Dynamic hybrid simulation using an electromagnetic shaker - Verma, Mohit; Sivaselvan, Mettupalayam V.; Rajasankar, J. (Journal of Structural Engineering, 2024)
This paper discusses a controller design strategy for the dynamic hybrid simulation using an electromagnetic shaker. A two-storey shear building is adopted as the system whose response is emulated using hybrid simulation. The bottom storey is taken as the physical subsystem while the top storey is taken as the virtual subsystem. A control law is derived such that the mechanical impedance of the electromagnetic shaker matches to that of the virtual subsystem. The control law is validated by comparing the frequency responses of the virtual subsystem and the electromagnetic shaker from the physical subsystem acceleration to the force transferred. Finally, the experimental validation of the controller design strategy is carried out by the dynamic hybrid simulation of the two storey structure. The frequency response obtained from the experiment and emulated system are found to be in good agreement with each other.